New method for adaptive echo cancellation in communication systems - ZHU You-lian1; LU You-hong2; SHI Guo-dong1 (Tongxin xuebao)
The advent of packetized audio transmission system has resulted in challenging requirements for echo cancellation technology.One key aspect of this technology is the need to estimate,quickly and accurately,the delay in an echo path in the transmission media.Delay estimation based on direct application of cross-correlation has poor performance and high implementation cost for the echo cancellation.A new method was presented in this paper.Input signals are bandpass filtered,downsampled,and cross-correlation function is computed via using the whitened signals.Theoretical analysis and experiment results show that the new delay estimation has resulted in higher performance and lesser computation cost than the traditional delay estimation.This method has a broad application in communication systems.